Assessment of crop residues-based electricity generation potential for energy security in Bangladesh. (September 2021) - Anand, Abhijeet; Aier, Imlisongla; Sakhiya, Anil Kumar; Kaushal, Priyanka
Abstract: About 65.82% of total electricity generation in Bangladesh come from domestic natural gas. Natural gas reserves are expected to deplete and become commercially unviable by 2030 at the current consumption rate, threatening the nation's energy security. Authors in this study investigated surplus crop residues availability and their electricity generation potential in 2018–19 and forecast to 2029–30 for establishing a biomass-based electricity generation system. It was estimated that 35.834 MT surplus crop residues could produce 42.560 TWh electricity, meeting 68.60% electricity demand in 2018–19. Forecast estimate showed that 50.561 TWh electricity generation potential of 42.553 MT surplus crop residues could supply 41.90% of forecasted electricity demand in 2029–30 in Bangladesh. Rangpur division possesses the largest share of crop residues availability and the Barisal Division the least. Results of this study could provide baseline data for establishing biomass-based electricity plants. Graphical abstract: Unlabelled Image Highlights: Crop residue energy potential was quantified for a biomass-based electricity system. Electricity generation potential is highest in Rangpur & least in Barisal division. Electricity generation from crop residue could meet 68.60% electricity demand. Crop residues could meet 41.90% of forecasted electrical energy demand in 2029–30.